GREEN ACCOUNTING IN UZBEKISTAN: SUSTAINABILITY AND INTERNATIONAL FINANCIAL REPORTING STANDARDS - Eshboyeva , Madina; Eshboyev , Temur; Saitov , Sirojiddin (Effective scientific journals, 2025)
Green accounting is a key instrument for integrating environmental aspects into financial reporting and supporting sustainable development. This article analyzes the role of green accounting in improving corporate transparency and alignment with international standards such as IFRS and GRI. The importance of implementing green accounting in Uzbekistan is highlighted in the context of global sustainability challenges.